Implementasi Metode Pembelajaran Play Based Learning dalam Materi Makhluk Hidup sebagai Sarana Pengembangan Kreativitas Siswa di SD - Firda Faizah; Ibnu Muthi (GURUKU : Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study investigates the implementation of the Play-Based Learning (PBL) method in Natural Science (IPA) instruction, specifically on the topic of living things, as a strategy to foster creativity among elementary school students. Employing a qualitative approach through a literature review method, data were collected from a range of scholarly sources, including books, peer-reviewed journals, and relevant educational documents. The findings demonstrate that PBL effectively promotes active, enjoyable, and meaningful learning experiences. It enhances students’ creativity through engaging activities such as exploration, experimentation, and the imaginative construction of living organisms. Moreover, PBL supports the development of divergent thinking, imagination, and collaboration skills. The approach aligns with the principles of the Merdeka Curriculum, which emphasizes differentiated instruction and student-centered learning. Therefore, PBL is recommended as a strategic pedagogical method for innovating science education in elementary schools to cultivate a creative, independent, and adaptive generation capable of responding to future challenges.